Le diable est dans les détails: Une analyse qualitative des valeurs et des croyances chez les membres du Temple Satanique - Colin, Mathieu (Archives de sciences sociales des religions, 2025)
Based on a cross-analysis of the history of ideas and previously unpublished qualitative material, this article examines the nature of beliefs within the Satanic Temple. The article first shows how the figure of Satan has been transformed and detached from its Christian tradition to support artistic and political demands on the fringes of traditional institutions. It was later adopted by non-theistic Satanist groups within an ultramodern reconfiguration of the spiritual and religious field. In this concept, the symbol of Satan represents a figure of freedom and emancipation from the traditional American religious environment. However, the article also explores the tensions surrounding the use of the terms of "religion", "spirituality" or "sacred", highlighting the need for doxastic autonomy and the significance of identity-based subcultures in the contexte to ultramodernity.